Definition of a matrix of the generalized parameters asymmetrical multiphase transmission lines - Suslov V.M. (Problems of the Regional Energetics, 2005)
Idle time, without introduction of wave characteristics, algorithm of definition of a matrix of the generalized parameters asymmetrical multiphase transmission lines is offered. Definition of a matrix of parameters is based on a matrix primary specific of parameters of line and simple iterative procedure. The amount of iterations of iterative procedure is determined by a set error of performance of the resulted matrix ratio between separate blocks of a determined matrix. The given error is connected by close image of with a margin error determined matrix.